A kind of anti-corrosion galvanized sheet and its preparation process and ship propeller using the anti-corrosion galvanized sheet
By setting a zinc-based phosphating film and an anti-corrosion coating with a micro-nano composite structure on the stainless steel plate of the ship propeller, the problem of corrosion of the ship propeller in the marine environment is solved, achieving better anti-corrosion capabilities and extending the service life. .
Patent Information
- Application Number
- CN202410328263.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-21
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-03-21
AI Technical Summary
Existing ship propellers are susceptible to seawater corrosion in marine environments, resulting in shortening their service life and insufficient anti-corrosion capabilities.
A technical solution is adopted to set zinc-based phosphating films and anti-corrosion coatings on both sides of the stainless steel plate. The anti-corrosion coating is made of silicone polyurethane resin, silica particles, nano-titanium dioxide and other raw materials to form a super ultra-thin phosphate coating with a micro-nano composite structure. Hydrophobic anti-corrosion coating.
It effectively prevents the diffusion of corrosive media into the anti-corrosion coating, enhances the anti-corrosion capability of the ship's propeller, and extends its service life.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of galvanized steel sheets, and more specifically, to an anti-corrosion galvanized sheet and a preparation process thereof, and a ship propeller using the anti-corrosion galvanized sheet. Background Art
[0002] With the development of the global economy and the increasing scarcity of marine resources, ships play an important role in promoting economic development, protecting the marine environment, and improving the efficiency of marine transportation. Ship propellers are devices that convert any form of energy into mechanical energy. Thrust is generated by rotating blades or jets (water), which can be used to drive vehicles forward or as a power source for other devices such as generators. Propeller propellers are referred to as propellers. The propeller is installed on the propulsion shaft below the waterline at the stern of the boat. The main engine drives the propulsion shaft to rotate together, sucking water from the suction surface of the blade and discharging it from the discharge surface. The reaction force of water is used to push the boat forward. It is widely used because of its low noise, no environmental pollution and small size. Seawater is a natural corrosive agent with a particularly high salt content and is highly corrosive. For ocean-going ships and some submarines that drift on the sea all year round, the ship propellers are always below the water surface and immersed in seawater for a long time. The corrosion caused by seawater is inevitable.
[0003] The main material of ship propellers is stainless steel. Ships are in the marine environment for a long time and are affected by seawater temperature, seawater salinity, marine atmospheric temperature, marine atmospheric humidity, etc. The stainless steel material will be corroded by seawater, thereby losing its protective effect and shortening the service life of the ship propeller.
[0004] With respect to the above-mentioned related technologies, the inventors have found that the anti-corrosion capability of current propellers for marine vessels needs to be improved. Summary of the invention
[0005] In order to improve the anti-corrosion ability of a ship propeller, the present application provides an anti-corrosion galvanized sheet and a preparation process thereof, and a ship propeller using the anti-corrosion galvanized sheet.
[0006] In the first aspect, the present application provides an anti-corrosion galvanized sheet, which adopts the following technical solution:
[0007] An anti-corrosion galvanized sheet comprises a stainless steel sheet, on both sides of which surfaces are provided with a zinc phosphate film and an anti-corrosion coating in sequence from the inside to the outside;
[0008] The anti-corrosion coating is formed by curing the anti-corrosion paint, and the anti-corrosion paint includes the following raw materials in parts by weight: 7-12 parts of silicone polyurethane resin, 2-7 parts of silicon dioxide particles, 1-5 parts of nano titanium dioxide, 2-5 parts of anti-settling agent, 14-36 parts of organic solvent, 0.3-0.8 parts of silane coupling agent, 0.1-0.3 parts of dispersant, 0.1-0.5 parts of defoaming agent, and 5-8 parts of filler.
[0009] By adopting the above technical scheme, the organic silicon polyurethane resin is tightly bonded with the zinc phosphating film after being cured and formed into a film, and the dispersed silicon dioxide particles and nano titanium dioxide are fixed, so as to construct an anti-corrosion coating with super hydrophobic properties having a micro-nano composite structure. The protrusions of the micro-nano composite structure can support water droplets and reduce the contact area. Air is retained in the holes to support the water droplets and hinder their spreading. In addition, the silicon dioxide particles and nano titanium dioxide can improve the wear resistance of the anti-corrosion coating and make the galvanized sheet durable. The organic silicon polyurethane resin penetrates and diffuses during the curing process to increase the bonding area, so that the anti-corrosion coating and the zinc phosphating film are tightly bonded, so that the anti-corrosion coating has good mechanical stability. The silane coupling agent can further increase the dispersion uniformity of the silicon dioxide particles, nano titanium dioxide and the organic silicon polyurethane resin after hydration and hydrolysis, and improve the interface strength between the anti-corrosion coating and the zinc phosphating film.
[0010] Optionally, the silicon dioxide particles are prepared by the following method:
[0011] In parts by weight, 1-2 parts of basalt flakes are added to a mixed solution of 45-90 parts of anhydrous ethanol and 15-30 parts of ammonia water, and ultrasonic dispersion is performed. 1.5-2.5 parts of ethyl orthosilicate are added, and the mixture is stirred at room temperature. 0.6-1.2 parts of 1H,1H,2H,2H-perfluorodecyltriethoxysilane is added to prepare a fluorinated silica sol.
[0012] Mix 2.5-3 parts of epoxy resin, 0.1-0.5 parts of carbonate quaternary ammonium salt and 2-4 parts of 3-aminopropyltriethoxysilane, heat to 45-60° C., stir for 3-4 hours, add the fluorinated silica sol and 0.8-0.9 parts of polyetheramine curing agent, stir evenly, dry and crush to obtain silica particles.
[0013] By adopting the above technical scheme, basalt flakes have a large number of hydroxyl groups, which can be physically combined with epoxy resin by hydrogen bonds and van der Waals forces, etc., and silica is grown on the surface of basalt flakes using sol, and then fluorinated with 1H, 1H, 2H, 2H-perfluorodecyl triethoxysilane to reduce the surface energy of silica, and grow nano-silicon dioxide in situ, which improves the surface roughness while avoiding the disordered accumulation of basalt flakes, which is beneficial to improve the adhesion strength of the anti-corrosion coating; then the fluorinated silica sol is modified with 3-aminopropyl triethoxysilane, and the modified fluorinated silica is combined with epoxy resin by covalent bonds and hydrogen bonds, and the added carbonate Salt-type quaternary ammonium salts are cationic corrosion inhibitors that increase the storage capacity of basalt flakes for cations. When the coating is immersed in a corrosive solution, the stored cations are slowly released and deposited on the surface of the substrate, reacting with the corrosive medium to form a thin film of corrosion products, becoming a better corrosion protection layer. The hydroxyl-rich halloysite on the surface is modified to obtain fluorinated silica particles for improving hydrophobic properties and anti-corrosion effects, which are then added to an epoxy resin matrix to ultimately produce silica particles with a core-shell structure of uniform size. Anti-corrosion coatings made with silicone polyurethane resins can effectively avoid cracking due to poor toughness of the coating, and can also improve adhesion and anti-corrosion effects.
[0014] Optionally, the nano titanium dioxide is hydrophobically modified by:
[0015] In parts by weight, 6-10 parts of nano titanium dioxide and 4-8 parts of silicon carbide are added to 10-20 parts of dopamine hydrochloride solution with a pH value of 8.5-9, heated at 60-80° C. and stirred for 7-8 hours, vacuum filtered, washed, dried, and ground to obtain a blended powder;
[0016] The blended powder is added to 200-250 parts of anhydrous ethanol, 2-4 parts of γ-mercaptopropyltrimethoxysilane are added, ultrasonic vibration is performed for 20-30 minutes, 20-40 parts of carboxyl carbon nanotubes are added, and the mixture is stirred at 100-120° C. for 2-4 hours, vacuum filtered, washed, dried and ground.
[0017] By adopting the above technical scheme, dopamine hydrochloride forms polydopamine with extremely strong adhesion in an alkaline environment, which is coated on the surface of nano titanium dioxide and silicon carbide to form a blended powder. The coating of polydopamine can increase the dispersibility of titanium dioxide and silicon carbide, and can also make the blended powder load better and more uniformly on the carboxyl carbon nanotubes. Polydopamine can also undergo a Melk addition reaction with γ-mercaptopropyltrimethoxysilane, and γ-mercaptopropyltrimethoxysilane is grafted onto the polydopamine-coated nano titanium dioxide and carbon nanotubes through the action of chemical bonds. The surface of silicon carbide is grafted with γ-mercaptopropyltrimethoxysilane, which further reduces the surface energy, making the surface energy of nano-titanium dioxide and silicon carbide loaded on the carboxyl carbon nanotubes low and hydrophobic. The high aspect ratio of the carboxyl carbon nanotubes can improve the strength and toughness of the coating, making the coating denser, improving corrosion resistance and good wear resistance. The polydopamine loaded on the carboxyl carbon nanotubes is coated with titanium dioxide and silicon carbide, and is tightly combined with the protrusions on the surface of the coating under the cross-linking reaction of polydopamine and silicone polyurethane resin. When the corrosive medium Cl in the water vapor - OH - , H + As the gas diffuses into the pores, the layered structure of the coating hinders the further diffusion of the corrosive medium into the substrate due to the many irregularly arranged titanium dioxide / silicon carbide-PDA-γ-mercaptopropyltrimethoxysilane / carboxyl carbon nanotubes inside the coating, effectively slowing down the corrosion process.
[0018] Optionally, the carboxyl carbon nanotubes are pretreated as follows:
[0019] The carboxyl carbon nanotubes are added to a zinc nitrate aqueous solution, ultrasonically vibrated, stirred at room temperature for 20-24 hours, centrifuged, washed, dried, and then added to a benzotriazole solution with a concentration of 5.5-6wt%, stirred for 20-24 hours, and dried at 50-80°C.
[0020] By adopting the above technical solution, carboxyl carbon nanotubes have a higher porosity and specific surface area. They are used as load containers to load zinc nitrate and benzotriazole. When the zinc cation corrosion inhibitor and benzotriazole coated in the coating are released, they will be deposited on the surface of the tin-plated steel plate, and can react with corrosive media such as water and oxygen that penetrate the coating to form a dense corrosion product film, thus becoming a better corrosion protection layer.
[0021] Optionally, the filler is selected from at least one of graphite, carbon fiber, activated carbon, talcum powder and organic bentonite.
[0022] Optionally, the dispersant is selected from at least one of polyacrylamide, polyethylene glycol fatty acid ester, sodium hexametaphosphate and methylpentanol;
[0023] The anti-settling agent is selected from at least one of polyamide wax, modified hydrogenated castor oil, polyolefin wax, castor oil derivatives and organic bentonite.
[0024] In a second aspect, the present application provides a preparation process of an anti-corrosion galvanized sheet, which adopts the following technical solution:
[0025] A preparation process of an anti-corrosion galvanized sheet comprises the following steps:
[0026] The stainless steel plate is soaked in alkali solution, cleaned, dried, and immersed in phosphating solution, and phosphated at 45-50°C for 10-15 minutes to form a zinc phosphating film on the surface of the stainless steel plate;
[0027] The organic silicon polyurethane resin, silicon dioxide particles, nano titanium dioxide, an anti-settling agent, an organic solvent, a silane coupling agent, a dispersant and a defoaming agent, and a filler are uniformly mixed to prepare an anti-corrosion coating;
[0028] The anti-corrosion coating is sprayed on the surface of the stainless steel plate with a zinc phosphate film, and dried at 80-100°C to form an anti-corrosion coating on the surface of the stainless steel plate with the zinc phosphate film.
[0029] By adopting the above technical scheme, after the stainless steel plate is soaked in alkali solution, a dense oxide film layer is formed, which plays a role in extending the service life. Then, phosphating is carried out on the stainless steel plate. After the phosphating film is formed, the method coating is sprayed on the zinc phosphating film to form an anti-corrosion coating with a micro-nano hierarchical structure on the stainless steel plate, thereby preventing the corrosive medium from diffusing and eroding into the interior of the anti-corrosion coating.
[0030] Optionally, the phosphating solution includes the following raw materials: 15-20 g / L zinc oxide, 13-17 g / L zinc nitrate, 22-26 g / L phosphoric acid, 12-14 g / L citric acid, 3-5 g / L sodium fluoride, and 5-7 g / L sodium dodecyl sulfate.
[0031] By adopting the above technical scheme, after the above raw materials are phosphated, the surface of the phosphating film formed is uneven, which can be tightly combined with the anti-corrosion coating to form a composite structure with a micro-nano hierarchical structure, and it is super hydrophobic, has a strong barrier effect on corrosive media, effectively hinders the penetration and diffusion of corrosive media and increases corrosion resistance, showing good durability.
[0032] Optionally, the spraying pressure is 3-4 bar, the spraying distance is 15-25 cm, and the thickness of the anti-corrosion coating is 65-75 μm.
[0033] By adopting the above technical scheme, the anti-corrosion coating on the surface of the stainless steel plate can effectively block the corrosive medium in seawater and increase the resistance to corrosion reaction. The low surface energy of the anti-corrosion coating can prevent the aqueous corrosive medium from infiltrating the surface, inhibiting the contact between the corrosive medium and the galvanized plate, thereby delaying the corrosion process.
[0034] In a third aspect, the present application provides a ship propeller using anti-corrosion galvanized sheet.
[0035] By adopting the above technical solution, the ship propeller is made of galvanized sheet and is not easily corroded when immersed in the ocean for a long time, thereby extending the service life of the ship propeller.
[0036] In summary, this application has the following beneficial effects:
[0037] 1. Since the present application adopts the method of setting a zinc phosphating film and an anti-corrosion coating on a stainless steel plate, the bonding strength between the anti-corrosion coating and the stainless steel plate can be increased. Moreover, the anti-corrosion coating is made of raw materials such as silicone polyurethane resin, silica particles and nano-titanium dioxide, which can form a micro-nano hierarchical structure, thereby trapping air to form a physical barrier, hindering the corrosive medium from diffusing and corroding into the interior of the anti-corrosion coating. Moreover, the surface energy of the anti-corrosion coating is low and its hydrophobicity is strong, which increases the resistance to the corrosive medium and reduces the tendency to corrosion.
[0038] 2. In the present application, it is preferred to grow silica in situ on basalt flakes and use fluorination treatment to reduce its surface energy and improve its dispersibility in epoxy resin. Then, a silane coupling agent is used to increase the bridge between silica and epoxy resin, thereby increasing the wear resistance of the silica particles. The carbonate-type quaternary ammonium salt gives the silica particles anti-corrosion ability, thereby producing silica particles with strong hydrophobicity, good wear resistance and corrosion resistance.
[0039] 3. In the present application, polydopamine is preferably used to coat nano-titanium dioxide and silicon carbide to improve the bonding strength of nano-titanium dioxide in the anti-corrosion coating, and the nano-titanium dioxide and silicon carbide coated with polydopamine are deposited on carboxyl carbon nanotubes. The anti-corrosion coating hinders the corrosive medium, and silicon carbide and carboxyl carbon nanotubes can also improve the wear resistance of the anti-corrosion coating. DETAILED DESCRIPTION
[0040] The following examples further illustrate the present application in detail.
[0041] Preparation Example 1-7 of Silica Particles
[0042] In Preparation Example 1, the epoxy resin is selected from Jining Huakai Resin Co., Ltd., model EP, the carbonate quaternary ammonium salt is selected from Hongli Chemical, model Arxada CarboShield 1000, and the polyetheramine curing agent is selected from Chuzhou Huisheng Electronics Co., Ltd., model D-230.
[0043] Preparation Example 1: (1) Add 2 g of basalt flakes to a mixed solution of 90 g of anhydrous ethanol and 30 g of ammonia water, disperse by ultrasonication for 1 h, add 2.5 g of ethyl orthosilicate, stir at room temperature for 5 h, add 1.2 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, stir for 2 h, and prepare a fluorinated silica sol;
[0044] (2) Mix 3 g of epoxy resin, 0.5 g of carbonate quaternary ammonium salt and 4 g of 3-aminopropyltriethoxysilane, heat to 60°C, stir for 3 h, add the fluorinated silica sol prepared in (1) and 0.9 g of polyetheramine curing agent, stir evenly, dry at 80°C, and crush to obtain silica particles with a particle size of 300 mesh.
[0045] Preparation Example 2: (1) Add 1 g of basalt flakes to a mixed solution of 45 g of anhydrous ethanol and 15 g of ammonia water, disperse by ultrasonication for 1 h, add 1.5 g of ethyl orthosilicate, stir at room temperature for 5 h, add 0.6 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, stir for 2 h, and prepare a fluorinated silica sol;
[0046] (2) Mix 2.5 g of epoxy resin, 0.1 g of carbonate quaternary ammonium salt and 2 g of 3-aminopropyltriethoxysilane, heat to 45°C, stir for 4 h, add the fluorinated silica sol prepared in (1) and 0.8 g of polyetheramine curing agent, stir evenly, dry at 80°C, and crush to obtain silica particles with a particle size of 300 mesh.
[0047] Preparation Example 3: Add 2 g of basalt flakes to a mixed solution of 90 g of anhydrous ethanol and 30 g of ammonia water, ultrasonically disperse for 1 h, add 2.5 g of tetraethyl orthosilicate, stir at room temperature for 5 h, add 1.2 g of 1H,1H,2H,2H-perfluorodecyltriethoxysilane, stir for 2 h, and obtain silica particles.
[0048] Preparation Example 4: The difference from Preparation Example 1 is that no carbonate-type quaternary ammonium salt is added.
[0049] Preparation Example 5: Mix 90 g of anhydrous ethanol, 30 g of ammonia water and 2.5 g of tetraethyl orthosilicate, stir at room temperature for 5 h, mix with 3 g of epoxy resin, 0.5 g of carbonate quaternary ammonium salt and 4 g of 3-aminopropyltriethoxysilane, heat to 60°C, stir for 3 h, add 0.9 g of polyetheramine curing agent, stir evenly, dry at 80°C, and crush to obtain silica particles with a particle size of 300 mesh.
[0050] Preparation Example 6: The difference from Preparation Example 1 is that 1H,1H,2H,2H-perfluorodecyltriethoxysilane is not added.
[0051] Preparation Example 7: Commercially available silicon dioxide particles, selected from Jinan Kasong Chemical Co., Ltd., model A300, particle size 300 mesh. Example
[0052] Example 1: An anti-corrosion galvanized sheet, comprising a stainless steel sheet, on both sides of which a zinc phosphating film and an anti-corrosion coating are sequentially arranged from the inside to the outside, the thickness of the stainless steel sheet is 1.2 mm, the anti-corrosion coating is formed by curing the anti-corrosion coating, and the amount of raw materials of the anti-corrosion coating is shown in Table 1, wherein the silicone polyurethane resin is selected from Xuzhou Yihuiyang New Materials Co., Ltd., model LP-900, the silica particles are prepared by Preparation Example 1, nano titanium dioxide is selected from Taizhou Aites Optical Materials Co., Ltd., model ATS-10, the anti-settling agent is polyamide wax, selected from Shenzhen Yoshida Chemical, model 6900-20X, the dispersant is polyacrylamide, the filler is talcum powder, the defoaming agent is BYK-028, the silane coupling agent is KH560, and the organic solvent is ethanol.
[0053] The method for preparing the above-mentioned anti-corrosion galvanized sheet comprises the following steps:
[0054] A stainless steel plate with a thickness of 0.4 mm is immersed in a sodium hydroxide solution with a concentration of 5 mol / L, and both sides are brushed with a brush to remove oil and impurities on the surface, immersed in water at room temperature, and the surface alkali solution is cleaned with a brush, and then immersed in hot water at 50°C and brushed with a brush, and placed in an oven at 70°C to remove surface moisture, and then immersed in a phosphating solution, and phosphated at 50°C for 15 minutes to form a zinc phosphating film on the surface of the stainless steel plate, wherein the phosphating solution includes the following raw materials: 20 g / L zinc oxide, 13 g / L zinc nitrate, 22 g / L phosphoric acid, 12 g / L citric acid, 5 g / L sodium fluoride, and 5 g / L sodium dodecyl sulfate;
[0055] The organic silicon polyurethane resin, silicon dioxide particles, nano titanium dioxide, an anti-settling agent, an organic solvent, a silane coupling agent, a dispersant and a defoaming agent, and a filler are uniformly mixed to prepare an anti-corrosion coating;
[0056] The anti-corrosion coating was sprayed on the surface of the stainless steel plate with a zinc phosphate film, and dried at 80°C to form an anti-corrosion coating with a thickness of 70 μm on the surface of the stainless steel plate with the zinc phosphate film. The spraying pressure was 4 bar and the spraying distance was 15 cm.
[0057] Table 1
[0058] Example 2: An anti-corrosion galvanized sheet, which is different from Example 1 in that the amount of anti-corrosion coating raw materials is as shown in Table 1, and the silica particles are prepared by Preparation Example 2.
[0059] Example 3: An anti-corrosion galvanized sheet, which is different from Example 1 in that the amount of anti-corrosion coating raw materials is as shown in Table 1.
[0060] Example 4: An anti-corrosion galvanized sheet, which is different from Example 1 in that the silica particles in the anti-corrosion coating are made from Preparation Example 3.
[0061] Example 5: An anti-corrosion galvanized sheet, which differs from Example 1 in that the silicon dioxide particles in the anti-corrosion coating are made from Preparation Example 4.
[0062] Example 6: An anti-corrosion galvanized sheet, which differs from Example 1 in that the silica particles in the anti-corrosion coating are made from Preparation Example 5.
[0063] Example 7: An anti-corrosion galvanized sheet, which differs from Example 1 in that the silica particles in the anti-corrosion coating are made from Preparation Example 6.
[0064] Example 8: An anti-corrosion galvanized sheet, which differs from Example 1 in that the silica particles in the anti-corrosion coating are made from Preparation Example 7.
[0065] Example 9: An anti-corrosion galvanized sheet, which is different from Example 1 in that the nano-titanium dioxide in the anti-corrosion coating is subjected to the following hydrophobic modification treatment:
[0066] Take a dopamine hydrochloride solution with a concentration of 1 g / L, adjust the pH to 8.5 with ammonia water, add 10 g of nano titanium dioxide and 8 g of silicon carbide to 20 g of the dopamine hydrochloride solution with a pH value of 8.5, heat and stir at 80°C for 8 hours, vacuum filter, wash twice with anhydrous ethanol and deionized water, dry, and grind to obtain a blended powder;
[0067] The obtained blended powder was added to 200g of anhydrous ethanol, 4g of γ-mercaptopropyltrimethoxysilane was added, ultrasonic oscillation was performed for 30min, 40g of carboxyl carbon nanotubes were added, and the mixture was stirred at 100°C for 4h. The mixture was vacuum filtered, washed twice with anhydrous ethanol and deionized water, dried, and ground. The carboxyl carbon nanotubes were selected from Beijing Dekedaojin Technology Co., Ltd., model CNT302.
[0068] Example 10: An anti-corrosion galvanized sheet, which is different from Example 1 in that the nano-titanium dioxide in the anti-corrosion coating is subjected to the following hydrophobic modification treatment:
[0069] Take a 1 g / L dopamine hydrochloride solution, adjust the pH to 9 with ammonia water, add 6 g of nano titanium dioxide and 4 g of silicon carbide to 10 g of the dopamine hydrochloride solution with a pH value of 9, heat and stir at 60° C. for 7 h, vacuum filter, wash twice with anhydrous ethanol and deionized water, dry, and grind to obtain a blended powder;
[0070] The obtained blended powder was added to 250g of anhydrous ethanol, 2g of γ-mercaptopropyltrimethoxysilane was added, ultrasonic oscillation was performed for 20min, 20g of carboxyl carbon nanotubes were added, and the mixture was stirred at 120°C for 2h. The mixture was vacuum filtered, washed twice with anhydrous ethanol and deionized water, dried, and ground. The carboxyl carbon nanotubes were selected from Beijing Dekedaojin Technology Co., Ltd., model CNT302.
[0071] Example 11: An anti-corrosion galvanized sheet, which is different from Example 9 in that the nano-titanium dioxide in the anti-corrosion coating is subjected to the following hydrophobic modification treatment:
[0072] 10 g of nano titanium dioxide and 8 g of silicon carbide were mixed to prepare a blended powder;
[0073] The obtained blended powder was added to 200g of anhydrous ethanol, 4g of γ-mercaptopropyltrimethoxysilane was added, ultrasonic oscillation was performed for 30min, 40g of carboxyl carbon nanotubes were added, and the mixture was stirred at 100°C for 4h. The mixture was vacuum filtered, washed twice with anhydrous ethanol and deionized water, dried, and ground. The carboxyl carbon nanotubes were selected from Beijing Dekedaojin Technology Co., Ltd., model CNT302.
[0074] Example 12: An anti-corrosion galvanized sheet, which differs from Example 9 in that silicon carbide is not added.
[0075] Example 13: An anti-corrosion galvanized sheet, which is different from Example 9 in that the nano-titanium dioxide in the anti-corrosion coating is subjected to the following hydrophobic modification treatment:
[0076] Take a 1 g / L dopamine hydrochloride solution, adjust the pH to 8.5 with ammonia water, add 10 g of nano titanium dioxide and 8 g of silicon carbide to 20 g of dopamine hydrochloride solution with a pH value of 8.5, heat and stir at 80°C for 8 h, vacuum filter, wash twice with anhydrous ethanol and deionized water, dry and grind.
[0077] Example 14: A corrosion-resistant galvanized sheet, which differs from Example 9 in that the carboxyl carbon nanotubes are pretreated as follows: 10 g of carboxyl carbon nanotubes are added to 20 ml of a 0.06 mol / L zinc nitrate aqueous solution, subjected to ultrasonic oscillation, stirred at room temperature for 24 h, centrifuged, washed, and dried, and then added to a 6 wt % anhydrous ethanol solution of benzotriazole prepared from 2.5 g of benzotriazole, stirred for 24 h, and dried at 50°C.
[0078] Comparative Example
[0079] Comparative Example 1: An anti-corrosion galvanized sheet, which differs from Example 1 in that no silicon dioxide particles are added.
[0080] Comparative Example 2: An anti-corrosion galvanized sheet, which differs from Example 1 in that no nano titanium dioxide is added.
[0081] Comparative Example 3: An anti-corrosion galvanized sheet, which differs from Example 1 in that no zinc phosphating film is provided. The preparation process of the anti-corrosion galvanized sheet is as follows: spraying the anti-corrosion coating on a stainless steel plate, and the spraying parameters and the thickness of the anti-corrosion coating are the same as those in Example 1.
[0082] Comparative Example 4: An anti-corrosion galvanized sheet, which differs from Example 1 in that no zinc phosphating film is provided, and the anti-corrosion coating is formed by curing the galvanized sheet coating. The galvanized sheet coating comprises the following components by weight percentage: 35% aqueous resin, 7% silicone agent, 1% dispersant, 0.5% wetting agent, 0.5% defoaming agent, 2% film-forming aid, 10% complexing agent, and 44% water. The aqueous resin is an acrylic resin, the silicone agent is potassium phenyldimethylsiliconate, the dispersant is a coupling agent dispersant, i.e., silane coupling agent 3-aminopropyltriethoxysilane, the wetting agent is alkyl polyether sulfate, the defoaming agent uses BYK024, the film-forming aid is propylene glycol methyl ether, and the complexing agent is 1,1-diphosphonic acid ethanol.
[0083] Performance testing
[0084] Anti-corrosion galvanized sheets were prepared according to the examples and comparative examples, and the performance of the anti-corrosion galvanized sheets was tested according to the following method. The test results are recorded in Table 2.
[0085] 1. Contact angle: The contact angle tester is used for testing at room temperature.
[0086] 2. Corrosion current density: A sodium chloride solution with a mass fraction of 3.5% was prepared as the corrosion medium. The Parstar 2273 electrochemical workstation was used to simulate the corrosion experiment. The working electrode was the test sample with an effective exposure area of 1 cm2. The auxiliary electrode was a platinum electrode and the reference electrode was a saturated calomel electrode. Before the test, the three-electrode system was immersed in a sodium chloride solution to reach a stable open circuit potential. The scanning rate of the polarization curve was 1 mV / s, and the scanning potential was -0.3 V to +0.3 V. The test data was analyzed using PowerSuite software to obtain the corrosion current density.
[0087] 3. Wear resistance: Use 1000-grit sandpaper (250g load) to rub the anti-corrosion coating 1000 times, then measure the contact angle and compare it with the contact angle of the initial anti-corrosion coating to calculate the decrease value.
[0088] 4. Adhesion: Use a tape peeling test. Cut a piece of seamless tape and press it to fit the surface of the sample completely. Then pull the tape along one side. Repeat the test 50 times, measure the contact angle, and compare it with the contact angle of the initial anti-corrosion coating to calculate the decrease value.
[0089] Table 2
[0090] It can be seen from the data in Table 2 that the silicon dioxide particles obtained in Preparation Example 1 and Preparation Example 2 are used in Example 1 and Example 2 respectively, and the amount of raw materials used in Example 3 is different from that in Example 1. It can be seen from the test on the galvanized sheet that its surface anti-corrosion coating has a large contact angle with water, strong hydrophobicity, small corrosion current density, strong corrosion resistance, and good wear resistance and peeling resistance.
[0091] In Example 4, the silica particles prepared in Preparation Example 3 were used. Compared with Preparation Example 1, epoxy resin and 3-aminopropyltriethoxysilane were not used. Table 2 shows that the hydrophobicity of the galvanized sheet prepared in Example 4 decreased, and the corrosion current density increased, the anti-corrosion effect weakened, and the wear resistance deteriorated.
[0092] Example 5 Compared with Example 1, the silica particles are prepared by Preparation Example 4, in which only the carbonate-type quaternary ammonium salt is not added. The surface hydrophobicity of the galvanized sheet prepared in this way decreases, and its corrosion current density increases, and the corrosion resistance is weakened.
[0093] In Example 6, the silica particles prepared in Preparation Example 5 were used. Compared with Preparation Example 1, the silica particles did not self-assemble on the basalt flakes, and 1H,1H,2H,2H-perfluorodecyltriethoxysilane was not added. Compared with Example 1, the wear resistance and adhesion of the galvanized sheet prepared in Example 6 were weakened, the contact angle was reduced, and the corrosion current density was increased, indicating that the self-assembly of silica particles on the basalt flakes can increase the roughness of the basalt flakes, improve the adhesion strength of the coating, and improve the wear resistance at the same time.
[0094] In Example 7, the silica particles prepared in Preparation Example 6 were used. Compared with Preparation Example 1, 1H,1H,2H,2H-perfluorodecyltriethoxysilane was not added, and the hydrophobicity of the prepared galvanized sheet decreased, and the anti-corrosion effect decreased.
[0095] In Example 8, commercially available silica particles were used. Compared with Example 1, the galvanized sheet produced thereby had a reduced contact angle with water, an increased corrosion current density, and reduced wear resistance.
[0096] Compared with Example 1, Examples 9 and 10 also use polydopamine, silicon carbide, carboxyl carbon nanotubes, etc. to pretreat nano-titanium dioxide, and the galvanized sheets prepared thereby are shown in Table 2. The hydrophobicity of the galvanized sheets prepared in Examples 9 and 10 is enhanced, the corrosion resistance is increased, and the wear resistance and interlayer adhesion are further improved.
[0097] In Example 11, compared with Example 9, no polydopamine was added during the pretreatment of the nano-titanium dioxide. It can be seen that the adhesion of the anti-corrosion coating on the galvanized sheet is reduced and the wear resistance is weakened.
[0098] In Example 12, compared with Example 9, silicon carbide was not added during the pretreatment of nano-titanium dioxide. Table 2 shows that the surface wear resistance of the galvanized sheet prepared in this way is reduced and the adhesion of the anti-corrosion coating is weakened.
[0099] In Example 13, when pretreating nano-titanium dioxide, no γ-mercaptopropyltrimethoxysilane and carboxyl carbon nanotubes were added, and only polydopamine was coated on the nano-titanium dioxide and silicon carbide. Table 2 shows that compared with Example 9, the galvanized sheet prepared in Example 13 has a smaller contact angle with water, a lower anti-corrosion performance, and weakened wear resistance and adhesion of the anti-corrosion coating.
[0100] Compared with Example 9, Example 14 also uses zinc nitrate and benzotriazole to pretreat the carboxyl carbon nanotubes. Table 2 shows that the corrosion current density of the galvanized sheet prepared in Example 14 is reduced and the anti-corrosion performance is enhanced.
[0101] Compared with Example 1, Comparative Examples 1 and 2 do not add silicon dioxide particles in Comparative Example 1, and do not add nano-titanium dioxide in Comparative Example 2. Compared with Example 1, the galvanized sheets prepared in Comparative Examples 1 and 2 have a decreased contact angle with water, weakened wear resistance, and weakened adhesion.
[0102] Compared with Example 1, in Comparative Example 3, no zinc phosphating film is provided, and the hydrophobicity of the anti-corrosion coating is still relatively high, but the corrosion current density increases, the anti-corrosion effect weakens, and the adhesion of the anti-corrosion coating decreases.
[0103] In Comparative Example 4, the anti-corrosion coating prepared by the prior art is adopted, and no zinc phosphating film is provided. Compared with Example 1, the anti-corrosion ability of the galvanized sheet prepared is poor.
[0104] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An anti-corrosion galvanized sheet, characterized in that: It includes a stainless steel plate, on both sides of which a zinc phosphate film and an anti-corrosion coating are sequentially arranged from the inside to the outside; The anticorrosive coating is formed by curing the anticorrosive coating, and the anticorrosive coating comprises the following raw materials in parts by weight: 7-12 parts of silicone polyurethane resin, 2-7 parts of silicon dioxide particles, 1-5 parts of nano titanium dioxide, 2-5 parts of anti-settling agent, 14-36 parts of organic solvent, 0.3-0.8 parts of silane coupling agent, 0.1-0.3 parts of dispersant, 0.1-0.5 parts of defoaming agent, and 5-8 parts of filler; The silicon dioxide particles are prepared by the following method: In parts by weight, 1-2 parts of basalt flakes are added to a mixed solution of 45-90 parts of anhydrous ethanol and 15-30 parts of ammonia water, and ultrasonic dispersion is performed. 1.5-2.5 parts of ethyl orthosilicate are added, and the mixture is stirred at room temperature. 0.6-1.2 parts of 1H,1H,2H,2H-perfluorodecyltriethoxysilane is added to prepare a fluorinated silica sol. Mix 2.5-3 parts of epoxy resin, 0.1-0.5 parts of carbonate quaternary ammonium salt and 2-4 parts of 3-aminopropyltriethoxysilane, heat to 45-60° C., stir for 3-4 hours, add the fluorinated silica sol and 0.8-0.9 parts of polyetheramine curing agent, stir evenly, dry and crush to obtain silica particles.
2. The anti-corrosion galvanized sheet according to claim 1, characterized in that: The nano titanium dioxide is hydrophobically modified by: In parts by weight, 6-10 parts of nano titanium dioxide and 4-8 parts of silicon carbide are added to 10-20 parts of dopamine hydrochloride solution with a pH value of 8.5-9, heated at 60-80° C. and stirred for 7-8 hours, vacuum filtered, washed, dried, and ground to obtain a blended powder; The blended powder is added to 200-250 parts of anhydrous ethanol, 2-4 parts of γ-mercaptopropyltrimethoxysilane are added, ultrasonic vibration is performed for 20-30 minutes, 20-40 parts of carboxyl carbon nanotubes are added, and the mixture is stirred at 100-120° C. for 2-4 hours, vacuum filtered, washed, dried and ground.
3. The anti-corrosion galvanized sheet according to claim 2, characterized in that: The carboxyl carbon nanotubes are pretreated as follows: The carboxyl carbon nanotubes are added to a zinc nitrate aqueous solution, ultrasonically vibrated, stirred at room temperature for 20-24 hours, centrifuged, washed, dried, and then added to a benzotriazole solution with a concentration of 5.5-6wt%, stirred for 20-24 hours, and dried at 50-80°C.
4. The anti-corrosion galvanized sheet according to claim 1, characterized in that: The filler is selected from at least one of graphite, carbon fiber, activated carbon, talcum powder and organic bentonite.
5. The anti-corrosion galvanized sheet according to claim 1, characterized in that: The dispersant is selected from at least one of polyacrylamide, polyethylene glycol fatty acid ester, sodium hexametaphosphate and methyl amyl alcohol; The anti-settling agent is selected from at least one of polyamide wax, modified hydrogenated castor oil, polyolefin wax, castor oil derivatives and organic bentonite.
6. The process for preparing the anti-corrosion galvanized sheet according to any one of claims 1 to 5, characterized in that: The following steps are involved: The stainless steel plate is soaked in alkali solution, cleaned, dried, and immersed in phosphating solution, and phosphated at 45-50°C for 10-15 minutes to form a zinc phosphating film on the surface of the stainless steel plate; The organic silicon polyurethane resin, silicon dioxide particles, nano titanium dioxide, an anti-settling agent, an organic solvent, a silane coupling agent, a dispersant and a defoaming agent, and a filler are uniformly mixed to prepare an anti-corrosion coating; The anti-corrosion coating is sprayed on the surface of the stainless steel plate with a zinc phosphate film, and dried at 80-100°C to form an anti-corrosion coating on the surface of the stainless steel plate with the zinc phosphate film.
7. The process for preparing the anti-corrosion galvanized sheet according to claim 6, characterized in that: The phosphating solution comprises the following raw materials: 15-20g / L zinc oxide, 13-17g / L zinc nitrate, 22-26g / L phosphoric acid, 12-14g / L citric acid, 3-5g / L sodium fluoride, 5-7g / L sodium dodecyl sulfate.
8. The process for preparing the anti-corrosion galvanized sheet according to claim 6, characterized in that: The spraying pressure is 3-4 bar, the spraying distance is 15-25 cm, and the thickness of the anti-corrosion coating is 65-75 μm.
9. A ship propeller using the anti-corrosion galvanized sheet according to any one of claims 1 to 5.
Citation Information
Patent Citations
Antiseptic super-hydrophobic paint for electric power system fittings and preparation method
CN103642378A
Rapid phosphating agent for galvanized steel sheets for color coating and application thereof
CN107326353A